Visitors’ satisfaction towards quality of services at Skytrex Adventure Melaka - Abd. Razak, Juwairiyah (2018)
Skytrex Adventure Melaka is one of the well-known recreation destination in Malaysia that offers tree to tree ‘sky-trekking’ obstacle. All visitors have their own level of satisfaction to recreation destination, especially in term of quality of services to ensure repeat purchase and loyalty. Thus, it is important to determine the expectation of the visitors and the performance of the provision of services to undertake any remedial or improvement actions. The main objective of the study is to examine the level of visitors’ satisfaction towards the quality of services provided in Skytrex Adventure Melaka. This study also determines the factors that influence visitors to Skytrex Adventure Melaka. The study used the modified Eco-tourist Services Quality (ECOSERVE) dimension to assess the services offered in Skytrex Adventure Melaka. Furthermore, this study used the Expectation-Performance Analysis or EPA to identify the services that require priority for improvement. Results indicated that, the level of visitors’ satisfaction on the overall quality of services at Skytrex Adventure Melaka is low and it was found that visitors were less satisfied with some services that provided. Out of the 21 items,14 items indicate that visitors were less satisfied and 2 items really needed urgent action which are providing comfortable waiting area and acceptable waiting time for next departure of activities. The results also showed that there were opportunities and recommendation that can be used to improve the service quality at Skytrex Adventure Melaka. Therefore, the findings of this study can provide useful information to the management of Skytrex Adventure Melaka for future improvement.